Family Planning Decision Making in People With Multiple Sclerosis - Bonavita, Simona; Lavorgna, Luigi; Worton, Hilary; Russell, Susan; Jack, Dominic (Frontiers in Neurology, 2021)
Introduction: The majority of people diagnosed with MS are of childbearing or child fathering age, therefore family planning is an important issue for both women and men with MS. Fertility and the course of pregnancy are not affected by MS; however, people with MS (pwMS) may have concerns that there will be a greater risk of complications to the mother and/or adverse pregnancy outcomes either due to the disease or to ongoing medication. This survey aimed to understand family planning decision making in pwMS and related unmet educational needs. Methods: A total of 332 pwMS across the USA, UK, France, Germany, Italy, and Spain were recruited from a specialist patient panel agency to participate in a smartphone-enabled standing panel. The 80-question survey focussed on decision making and information sources for pwMS regarding family planning, as well as behavior during and after pregnancy. Male patients with MS did not respond to specific questions on pregnancy. Survey results were directly compared with the 2016 US and 2010 UN census data. Results: pwMS were more likely to have no children than the general population, particularly in the subgroup of patients aged 36–45 years. A total of 56% of pwMS reported that the disease affected, with different degrees of impact, their family planning decision making. Of these, 21% significantly changed their plans for timing of pregnancy and the number of children, and 14% decided against having children. Participants indicated that healthcare professionals were the primary source of information on family planning (81% of responses). The timing of planned pregnancy was not considered when selecting treatment by 78% of participants. Conclusion: MS was found to significantly impact family planning decision making, with pwMS significantly less likely to have children in comparison with the general population.